Islamic Constructs of Nursi’s Perspective and Their Impacts on Psychology - Mustafa Tekke (Tarbiyah Departement collaboration with AMCA, 2017)
This study proposed new constructs to the field of Islamic psychology. It is particularly noteworthy to articulate the views of Said Nursi in the context of Islamic psychology. Based on fundamental aims of Qur’an, it clearly shows that Tawhid (Belief in God), Nubuwwa (Awareness of Prophetic Teaching), Hashr (Belief in Resurrection), and Ibadah (Worship) as for main constructs of Qur'an greatly influential on a person's belief and thought.The proposed four constructs were thoroughly scrutinized to determine the possible meanings with human belief and thought. In line with chosen method, this paper applies the views of Nursi as a device for synthesizing arguments. Islamic psychology clearly indicates the Tawhid and Nubuwwa, called shahadah, are fundamental of Islamic belief and thought and included with awareness of hereafter and doing worship. The other constructs of Hashr and Ibadah are also essential for an Islamic psychology model for understanding human personality. They were conceptually evaluated within the context of psychology, as indicatives of the concept of Islamic personality. These four constructs can be interpreted as inner experience depicting human’s emotions, desires, wishes, and intentions. Thus, they are strongly suggested to employ in newly developing Islamic personality scales.